Massive misuse of antibiotics by university students in China: a cross-sectional survey. (October 2016) - Wang, Xiao-Min; Zhou, Xu-Dong; Hesketh, Therese
Abstract: Background: Antimicrobial resistance is one of the greatest threats to global population health this century, and is a major contributor to rising healthcare costs worldwide. The primary cause of this resistance is antibiotic misuse, especially routine inappropriate use of antibiotics for self-limiting illnesses. In China, over prescribing of antibiotics is pervasive leading to very high and increasing rates of antimicrobial resistance in both hospital-acquired and community-acquired infections. The aim of this study was to explore the knowledge and behaviours of university students in relation to antibiotic use in six Chinese provinces. Methods: A stratified, cluster-random sampling method was used to select students across six universities in six provinces (Zhejiang, Wuhan, NanKai, Jilin, Guizhou, and Lanzhou Universities). An anonymous online survey tool, Wen Juan Xing, was used to collect data. Students completed the survey using a smartphone application. χ 2 test and logistic regression model were used to assess associations between knowledge and behaviour. Patient consent and ethical approval were obtained for this study. Findings: 11 192/11 459 (98%) students completed the questionnaire. Knowledge of antibiotics and their appropriate use was poor: only 236/11 192 (2%) answered all 13 questions correctly. In terms of healthcare-seeking behaviour, of 3337/11 192 (30%) students who were ill in the preceding month, 913/3337 (27%) went to see a doctor and 600/913 (66%) of these students were prescribed antibiotics; 1711/3337 (51%) treated themselves, 507/1711 (30%) of these with antibiotics. 7057/11 192 (63%) of students keep antibiotics at home. Of 6269/11 192 (56%) students who tried to buy antibiotics from a drugstore in the preceding year, 4133/6269 (66%) tried to do so without prescription and 3964/4133 (96%) succeeded. Students who keep antibiotics at home are almost 5 times more likely to self-treat with antibiotics (OR=4·90, 95% CI 3·48–6·90). Interpretation: Demand for antibiotics has an important role in the excess use of antibiotics among university students in China. An education campaign about proper use of antibiotics is an urgent priority and should involve both health professionals and the general public. Existing regulations prohibiting pharmacists to sell antibiotics over-the-counter must be enforced. Funding: None